Unveiling the experiences of young people in foster care: perspectives from Portugal and Nigeria - Adeboye, T. K.; Guerreiro, M. D.; Höjer, I. (International Social Work, 2019)
This article examines the lived experiences of young people in the process of leaving the care of SOS Children’s Villages in both Nigeria and Portugal. Interviews were conducted with 12 young people and data were analysed using content analysis. Young people’s lived experiences were captured in three emerging dimensions of past, present and future experiences. The study recommends resolving young people’s childhood conflicts towards a successful transition into adulthood. It also has implications for policy practice in tailoring the present experiences in preparing young people for the demands of life after care.